Measurement Of Halal Certification Quality Of Service On Business Satisfaction In Banda Aceh City - Sari, Nilam; Azimah Dianah; Hafidhah; Khairun Nisa (Jurnal Internasional Ekonomi Islam, 2025)
Introduction: Business actor satisfaction is a feeling based on expectations regarding a product or service. Serve, and the level of satisfaction felt will vary according to the conformity with which service exists. If that reality exceeds hope, then the service can be said to be of good quality. If it is below expectations, the service can be bad; if it is above expectations, it can be said to be good. That service is satisfying. Objective: This study aims to research halal certification services to satisfy business actors in Banda Aceh City. Are these certification services quality indicators influencing the satisfaction of business actors as customers? Method: This study uses a quantitative approach with the Structural Equation Model - Partial Least Squares (SEM-PLS) method. The test was conducted using the Smart PLS 3.0 application, with the respondent category being business actors. One hundred business actors in Banda Aceh City have issued halal certification for their products, and there are 100 people. Results: The research country found that all variables, namely reliability, responsiveness, certainty, empathy, tangible evidence, and price, significantly influence business actors’ satisfaction. Implications: This shows that improving the quality of halal certification services in Banda Aceh City can also increase business actors' satisfaction